2015
DOI: 10.1177/183693911504000107
|View full text |Cite
|
Sign up to set email alerts
|

Organisational Capacity Building: Readiness for Change in Australian Child Care

Abstract: THIS STUDY ASSESSES FAMILY day care educators' readiness for increasing their knowledge and skills in promoting children's social and emotional wellbeing by applying the Transtheoretical Model of Change conceptual framework. Forty-eight educators in one family day care scheme, in a low socioeconomic area of Victoria, Australia participated in telephone interviews. Their readiness to improve children's social and emotional wellbeing was classified according to the stages of change model. A high proportion of ed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 15 publications
(20 reference statements)
0
1
0
Order By: Relevance
“…Despite working in partnership with the one FDC scheme for years prior to the trial, and including educators at every stage of developing the Thrive program, the intervention sample was smaller than anticipated and skewed towards educators who were more highly qualified. In a previous study, we demonstrated that almost all educators reported that they needed to increase their knowledge about children's social and emotional wellbeing (Davis et al, 2015), and they indicated that they would be keen to be a part of a new program. When it came time to recruit however, many reported that they were too busy to attend the workshops.…”
Section: Difficulties and Complexitiesmentioning
confidence: 90%
“…Despite working in partnership with the one FDC scheme for years prior to the trial, and including educators at every stage of developing the Thrive program, the intervention sample was smaller than anticipated and skewed towards educators who were more highly qualified. In a previous study, we demonstrated that almost all educators reported that they needed to increase their knowledge about children's social and emotional wellbeing (Davis et al, 2015), and they indicated that they would be keen to be a part of a new program. When it came time to recruit however, many reported that they were too busy to attend the workshops.…”
Section: Difficulties and Complexitiesmentioning
confidence: 90%